Stevens Johnson Sindrome (SJS) in a Patient Presenting with Acute Pharyngitis - Ristyana, Sabira Husna; Nadiroh, Ulayya Azzah; Adji, Iwan Setiawan (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this report is to present a case of Stevens Johnson Syndrome (SJS) in a Patient with Acute Pharyngitis, analyzing its etiology, risk factors, clinical symptoms, diagnostic tests, and treatment. This report also highlights the importance of prevention and proper management to improve the prognosis of the patient. Methodology: The methodology used in this report is a clinical case study. Data were collected through anamnesis, physical examination, and supporting examinations such as laboratorium. The patient's management was analyzed based on existing medical theories and appropriate treatment was provided according to the patient's condition. Results: The patient was diagnosed with acute pharyngitis with a differential diagnosis of Steven Johnson syndrome, with complaints of sore throat since 5 days ago. Blood laboratory results; leukocyte count 10.75 thousand/ul, leukocyte differential count; neutrophils 78.7% (H), lymphocytes 12.9% (L), eosinophils 0.9%, NLR 6.10% (H). Patients received therapies such as neurobion injections, metamizole injections, and dexamethasone injections. The patient was consulted to a dermatovenerology because the patient was suspected of having Steven Johnson Syndrome. So it is true that the patient has Steven Johnson Syndrome. The therapy given by the dermatovenerology was a 10 mg dexamethasone injection, followed by 5 mg every hour. Other therapies were stopped. The patient had a history of taking medication for headaches which was identified as a significant risk factor for developing the condition. Applications/Originality/Value: This report provides insights into the importance of early diagnosis and proper management in steven jhonson syndrome. sore throat most frequently recorded as a prodromal symptom for SJS, before the onset of skin rashes and oral cavity lesions. Painful skin rash when pressed and Nikolsky's sign are indicators to suspect Stevens-Johnson syndrome. Delayed management of SJS can be fatal, so misdiagnosis must be avoided. The findings can be useful for healthcare professionals to understand clinical signs and effective treatment approaches for similar cases. The study emphasizes the need for preventive measures. A thorough investigation of the drug usage history must be conducted to establish the diagnosis and determine the management plan. Management through multidisciplinary collaboration is highly expected for the patient's recovery.